The Effect of Marketing and Business Capital Digitalization on MSME Performance in Ambon City: Multiple Regression Analysis Approach (Digital Innovation : International Journal of Management, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute the backbone of Indonesia's national economy, contributing approximately 61% of GDP and absorbing 97% of the total workforce; however, the majority of MSME actors, particularly in eastern Indonesia, continue to face structural barriers in digital technology adoption and capital access that constrain optimal business performance. This study aims to analyze the partial and simultaneous effects of marketing digitalization and business capital on MSME performance in Ambon City. A quantitative approach with associative-causal design was employed, involving 30 respondents selected through purposive sampling from active MSME operators in Ambon City. Data were collected via a five-point Likert scale questionnaire and analyzed using multiple linear regression with IBM SPSS version 26, preceded by validity, reliability, and classical assumption tests. Results demonstrate that marketing digitalization exerts a positive and significant partial effect on MSME performance (t = 8.060; sig. = 0.000; β = 1.061), establishing it as the most dominant predictor in the model. Conversely, business capital shows no significant partial effect (t = 0.746; sig. = 0.462), attributable to the homogeneity of capital access among MSME actors in archipelagic regions. Simultaneously, both variables significantly influence MSME performance (F = 287.070; sig. = 0.000), with an exceptionally high R Square of 0.955, indicating that 95.5% of performance variance is collectively explained by the two predictors. These findings underscore the critical role of digital marketing capabilities over financial resources alone in archipelagic contexts. It is recommended that the Ambon City Government integrate digital marketing literacy training programs synergistically with inclusive financing schemes to comprehensively strengthen MSME competitiveness across the Maluku archipelago.